Difficult Diagnoses in Hyperkinetic Disorders – A Focused Review - Cardoso, Francisco (Frontiers in Neurology, 2012)
Hyperkinesias are heterogeneous conditions that share the feature of production of involuntary, abnormal, excessive movements. Tremor, dystonia, and chorea are amongst the most common of these phenomena. In this focused review there is a discussion of difficult issues in hyperkinesias. The first one is the differential diagnosis between essential tremor (ET) and Parkinson’s disease (PD). They are readily distinguishable in the majority of patients but in a few subjects ET coexist with parkinsonian features whose underlying mechanism remains to be determined. The second topic of the review is dystonic tremor. Although increasingly diagnosed and reported as accounting for the majority of scans without evidence of dopaminergic deficits, its diagnostic criteria are ill-defined and differentiation from PD and ET can be challenging. In the last section, there is a discussion of the differential diagnosis of Sydenham’s chorea (SC), the most common cause of chorea in children. In a few patients, vascular disease, systemic lupus erythematosus, and primary antiphospholipid antibody syndrome can mimic SC.